Reciprocal control of excitatory synapse numbers by Wnt and Wnt inhibitor PRR7 secreted on exosomes - Sang H. Lee; Seung Min Shin; Peng Zhong; Hyun-Taek Kim; Dong-Il Kim; June Myoung Kim; Won Do Heo; Dae-Won Kim; Chang-Yeol Yeo; Cheol-Hee Kim; Qing-song Liu (Nature Communications, 2018)
Wnts are important for synapse formation and maintenance. Here, the authors show that proline-rich 7 (PRR7) is a Wnt inhibitor that is secreted via exosomes to regulate excitatory synapse numbers.